Understanding cardiovascular disease in day-to-day living for African people: a qualitative metasynthesis - Seifu Nigussie Tulu; Nasser Al Salmi; Jacqueline Jones (BMC, 2021)
Abstract Background Globally, cardiovascular disease (CVD) accounts for 45% of all chronic non-communicable disease deaths and 31% of all deaths. CVD has remained the primary cause of death in the world for the past fifteen years. Compared to other continents, CVD and its risk factors are highly prevalent in Africa, but the continent also displays a low-level of knowledge and awareness of CVD, and poor perception of its risk factors. Little research has been done on the connection between the daily lived experiences of African people and the high prevalence and poor perception of CVD and its risk factors on the African continent. The aim of this study is to provide an in-depth understanding of the daily, lived experiences of African people and the connections between these experiences and the prevention, control, and management of CVD and its risk factors. Methods A systematic search was performed in PubMed, CINAHL, EMBASE, Psych INFO, and Web of Science databases to identify published English qualitative studies of CVD and its risk factors. Qualitative metasynthesis included structured techniques of data immersion and quality appraisal, thematic synthesis, and reciprocal translation. Results Seven studies met the inclusion criteria. Four major themes were identified from the metasynthesis: 1) understanding and beliefs about CVD; 2) perceived causes/risk factors for CVD; 3) understanding and belief about obesity; 4) perceived treatment options for CVD. The metasynthesis identified a consistent disconnect among African people between seeing CVD as a deadly and chronic disease and their perceptions of the minimal signs and symptoms of the disease in the early stages. This was further compounded by the gap between traditional healers and health care professionals. Conclusions Perceptions of CVD, its risk factors, and treatments were influenced by religious and cultural factors. Given the minimal signs and symptoms experienced in the early stages of the disease, there was a consistent disconnect among African people between seeing CVD as a deadly and chronic illness. Further investigations of the religious and cultural influences and educational programs related to these areas of disconnect are needed to improve the knowledge, attitudes, and beliefs of African people.